Project-based Learning Strategy: An Innovative Proposal for Local Education System - Mercedes López López, María; Vegas Meléndez , Hilarión; Rodríguez Gámez, María (International Journal of Psychosocial Rehabilitation, 2020)
The educational and professional approach leads the individual to create strategies that allow them to develop knowledge in an active way, in order to trigger solutions to a problem. The purpose of this research is to study Project Based Learning (ABP), as an innovative proposal for the Local Education System, valuing the need that students have, to form meaningful learning in them, with critical, analytical and reflective thinking. The cognitive process also influences the application of ABP, such as the development of emotional intelligence that is part of the competencies and skills, which the teacher must encourage, to strengthen life expectancy, the training process, and the social environment. The applied methodology was carried out, by means of the field study, the direct observation, that in a qualitative and quantitative way, the educational institutions of Manta were studied, surveying thirty-four teachers and one hundred and forty-three students, to give precision, efficacy and efficiency to the results, the deductive-inductive, heuristic methods, induced that according to the applied surveys, it can be known that 29% of teachers use the project-based learning methodology, evidencing that 38% of students develop critical, analytical and reflective thinking through meaningful learning. As for the students, it was evidenced by 28% that when carrying out a project they are interested in knowing the study problem.